The Impact of Fintech, E-Commerce, and Skills on MSME Financial Performance: Financial Literacy and Trust as Mediators - Bintang Surya Putra; Abdul Mukti Soma (Al-Qalam Institute, 2025)
The rapid expansion of digital technology has transformed business practices among Micro, Small, and Medium Enterprises (MSMEs), yet its impact on financial performance remains inconclusive. Despite increasing adoption of financial technology and e-commerce, many MSMEs continue to face financial sustainability challenges, as reflected in the rising non-performing loan ratio. This study aims to examine the direct and indirect effects of financial technology, e-commerce adoption, and entrepreneurial skills on the financial performance of MSMEs, incorporating financial literacy and trust as mediating variables. A quantitative approach was employed, using survey data collected from 200 MSME actors in West Java, and the data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that financial technology and entrepreneurial skills have a positive and significant direct effect on financial performance. In contrast, e-commerce adoption does not directly influence performance but becomes significant when mediated by financial literacy and trust. Furthermore, both mediators strengthen the indirect effects of digital adoption and entrepreneurial capabilities on financial outcomes. This study contributes to the literature by highlighting the critical role of cognitive and relational factors in enhancing the effectiveness of digital transformation among MSMEs.